Prevalence of menstrual disorder among college girls and correlation with body mass index - J., Jeevitha K.; S., Rajarajeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Menstrual irregularity is the most common gynaecological disorder in all age group. Adolescence is a transitional period between childhood and adulthood and involves physical, biological and psychosexual changes and is characterized by hormonal changes. Aim of this study was to find out the prevalence of menstrual abnormality in college girls in Madurai and their association with their Body mass Index (BMI). Methods: A cross sectional study was conducted among 200 girls of age group 18-22 years in a college in Madurai after getting their consent from college authorities and students. All details regarding their age of menarche, type of menstrual disorder and their BMI, stress factors were collected. The results were compared using chi square test and the pattern of menstrual abnormality and its relation with BMI and with stress was obtained. Results: The average age of menarche was 13.38 years in our study, irregular cycle was present in 47.5%, dysmenorrhoea was the commonest disorder and accounts for 26% students requiring medical treatment. Underweight students have irregular cycles compared to other groups. Stress had a significant correlation with menstrual irregularity. Conclusions: Many students in our study was under obese category, lifestyle modification like regular exercise, avoiding junk food and promoting healthy eating habits should be emphasised among students to have a healthy life. Students should also be informed about menstruation, physiological changes and its importance.